Maire Tecnimont : the creation of NextChem - Chesbrough, Henry, (SAGE Business cases., 2021)
This case shows how Maire Tecnimont, a large engineering design and construction company in Italy, chose to launch a new subsidiary company NextChem. NextChem gathers together the various green and renewable energy activities in the company, and places them together under a single organization.The case describes Maire Tecnimont as a company, outlines some of its innovation processes, and explores the business opportunities arising from Green Chemistry. While there is some technology discussion as well, the primary focus is the shift in capital expenditures and staffing costs available under Green Chemistry. Digital technologies also feature prominently as well.